1971
DOI: 10.1111/j.1365-2621.1971.tb02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Infrared Spectroscopic Determination of Degree of Unsaturation of Fats and Oils

Abstract: SUMMARY– Infrared spectra of various fats and oils were determined. Ratios of absorbance at 3.3μ (olefinic C—H stretching band) to absorbance of other characteristic triglyceride absorption bands were calculated. Relationships between these ratios and unsaturation, as estimated by iodine value, were determined. Analyses of 25 fats and oils showed that the ratio of absorbance at 3.3μ to absorbance at 3.5μ (aliphatic C—H stretching band) and iodine value were linearly related and exhibited a correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 1 publication
3
18
0
3
Order By: Relevance
“…This study was later confirmed by the results achieved by other authors who proposed mid-infrared spectroscopy as a technique to determine the degree of unsaturation (Chapman 1965). Later, Arnold and Hartung (1971), using the ratio of absorbances at 3030 cm-I ( = C-H vibration) and 2857 em -I (>CH 2 vibration), showed the potential of a mid-infrared instrument equipped with a transmission cell for iodine value determinations in fats and oils. Using the absorbance at wavenumbers from the same region (3010 cm-I and 2854 cm-I), Afran and Newbery (1991) demonstrated the potential of the FT-MIR instrument coupled with an ATR accessory.…”
Section: Determination Of Unsaturation Degree: Iodine Valuesupporting
confidence: 72%
“…This study was later confirmed by the results achieved by other authors who proposed mid-infrared spectroscopy as a technique to determine the degree of unsaturation (Chapman 1965). Later, Arnold and Hartung (1971), using the ratio of absorbances at 3030 cm-I ( = C-H vibration) and 2857 em -I (>CH 2 vibration), showed the potential of a mid-infrared instrument equipped with a transmission cell for iodine value determinations in fats and oils. Using the absorbance at wavenumbers from the same region (3010 cm-I and 2854 cm-I), Afran and Newbery (1991) demonstrated the potential of the FT-MIR instrument coupled with an ATR accessory.…”
Section: Determination Of Unsaturation Degree: Iodine Valuesupporting
confidence: 72%
“…These are fast, usually require little cost and time, and provide a great deal of information. Unsaturation degree of edible oils and fats has been found to be closely related to the absorbance of some bands of the Fouriertransformed infrared spectrum [13][14][15][16][17][18][19]. It has also been proved that frequency values of some bands are also closely related to the proportions of saturated, monounsaturated and polyunsaturated acyl groups [20,21].…”
Section: Introductionmentioning
confidence: 98%
“…In previous papers the usefulness of spectroscopic techniques, such as Fourier transform infrared spectroscopy, in characterization of edible oils and fats have been demonstrated [6][7][8][9][10][11][12]. 1 H nuclear magnetic resonance ( 1 H NMR) in the study of oils and fats has already been reviewed [13], and the usefulness of the shape and chemical shifts of the 1 H NMR spectra signals in discriminating between oils of different compositions has been demonstrated [14].…”
Section: Introductionmentioning
confidence: 99%